An Integrative Analysis Reveals the Underlying Association Between CTNNB1 Mutation and Immunotherapy in Hepatocellular Carcinoma - Mo, Zhuomao; Wang, Yongdan; Cao, Zhirui; Li, Pan; Zhang, Shijun (Frontiers in Oncology, 2020)
Background: Tumor mutational burden (TMB) was verified to be closely associated with immune checkpoint inhibitors, but it is unclear whether gene mutation has an effect on immunotherapy of hepatocellular carcinoma (HCC). This research aimed to investigate the underlying correlation between gene mutation and immunotherapy in HCC. Methods: The somatic gene mutation data and gene expression data were retrieved from International Cancer Genome Consortium database and The Cancer Genome Atlas database. The mutational genes were selected by the intersection of three cohorts and further identified using survival analysis and TMB correlation analysis. After the identification of key mutational gene, we explored the correlation between gene mutation and immune cells infiltration, gene mutation and immune inhibitors. The signaling pathways associated with gene mutation were confirmed through Gene Set Enrichment Analysis. Furthermore, the survival analysis and mutational analysis basing on TCGA cohort were performed for the validation of included gene. Results: As one of the frequently mutational genes in HCC, CTNNB1 was finally included in our research, for which it showed the significant result in survival analysis and the positive association with TMB of three cohorts. Meanwhile, the validation of TCGA showed the significant results. Furthermore, NK cell and Neutrophil was found to significantly infiltrated in CTNNB1 mutation group from two cohorts. Besides, further analysis demonstrated that four types of immune inhibitors (CD96, HAVCR2, LGALS9 and TGFB1) were downregulated in CTNNB1 mutation group. Conclusion: Our research firstly revealed the underlying association between CTNNB1 mutation and immunotherapy, and we speculated that CTNNB1 mutation may modulate NK cells by affecting CD96. However, more functional experiments should be performed for verification.